Performa Peningkatan Lemak Dan Asam Lemak Linoleat Dari Daphnia Sp. Dengan Menggunakan Fermentasi Kotoran Burung Puyuh, Roti Afkir, Dan Ampas Tahu - Syaiful Anwar; Johannes Hutabarat; Vivi Endar Herawati (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2018)
Daphnia sp. was natural feed which could adequate the needs of fish fry growth. Fats and fatty acids was main factor which very influenced the success of reproduction and live for hatched larva fish. Fats had important role as the main source. The lack of essencial fatty acid could impact the decrease of fish growth and reproduction. The purpose of this research were to found out the best treatments and the effect of fermented quail feces, bread waste, and tofu waste towards the growth, and increased fats and linoleic fatty acid from Daphnia sp.. The methods of this research was used experimental method and complete randomize design with 4 treatments and 3 repetitions, with density of 100 ind./litre. The treatments which used on this research were treatment A (50% bread waste, 50% tofu waste, and 0% quail feces), treatment B (25% bread waste, 50% tofu waste, and 25% quail feces), treatment C (50% bread waste, 25% tofu waste, and 25% quail feces), and treatment C (25% bread waste, 25% tofu waste, and 50% quail feces) with total combination amount of 200 grams/litre. The data that observed were population of Daphnia sp., fatty acid value, and linoleic fatty acid value. The result of this research showed that Daphnia sp. growth population was valued 502,22 ind/ml – 1949,44 ind/ml, whereas the increasing of fat value from 6,26% became 8,15% and linoleic fatty acid from 0,91% become 6,14%. Acording to the research result could be concluded that the additition of fermented quail feces, and tofu waste gave differences towards the growth, with the fat value increased of Daphnia sp. was 1,89% and linoleic fatty acid was 5,23% and the best treatment for growth and linoleic fatty acid value was the treatment C (50% bread waste, 25% tofu waste, and 25% quail feces) and treatment A (50% bread waste, 50% tofu waste, and 0% quail feces) for the fat value of Daphnia sp.Keyword: Daphnia sp.; Fats; Linoleic Fatty Acid; Fermentation